2017
DOI: 10.1302/2046-3758.65.bjr-2017-0287.r1
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of rotational control designs in promoting torsional stability of hip fracture fixation

Abstract: ObjectivesFractures of the proximal femur are a common clinical problem, and a number of orthopaedic devices are available for the treatment of such fractures. The objective of this study was to assess the rotational stability, a common failure predictor, of three different rotational control design philosophies: a screw, a helical blade and a deployable crucifix.MethodsDevices were compared in terms of the mechanical work (W) required to rotate the implant by 6° in a bone substitute material. The substitute m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
4
8
0
Order By: Relevance
“…A transcondylar screw that minimized the loss of reduction from rotation would be advantageous and may allow for the type and necessity of anti‐rotational implants to be reconsidered. Human studies focused on evaluating the impact of rotational stability on scaphoid and intertrochanteric fractures showed that the screw design is a contributing factor 35,36 . A secondary fixation was not included in the current construct model, which will affect the clinical relevance of the results; however, the purpose of the study was to evaluate the different screw types in isolation to understand the influence of the new screw thread design.…”
Section: Discussionmentioning
confidence: 99%
“…A transcondylar screw that minimized the loss of reduction from rotation would be advantageous and may allow for the type and necessity of anti‐rotational implants to be reconsidered. Human studies focused on evaluating the impact of rotational stability on scaphoid and intertrochanteric fractures showed that the screw design is a contributing factor 35,36 . A secondary fixation was not included in the current construct model, which will affect the clinical relevance of the results; however, the purpose of the study was to evaluate the different screw types in isolation to understand the influence of the new screw thread design.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has shown considerable biomechanical advantages over standard cancellous screw placement [ 29 ], and when used for displaced fractures in 207 patients was clinically associated with very low complication rates, such as an AVN rate of only 0.5% [ 31 ]. New implants have been developed primarily for extracapsular hip fractures, such as the X-Bolt (X-Bolt, Dublin, Ireland) using deployable flanges, and show biomechanical improvements over SHS, especially for rotational stability in low density bone [ 32 ]. However, clinical validations of these findings are awaited in intracapsular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…New fixations have been tried. A self-locking blade , a medial buttress plate (Mir andCollinge, 2015, Giordano et al, 2019), a deployable crucifix (Gosiewski et al, 2017) and a perforated H-beam (Jafarov et al, 2019) have been tested.…”
Section: Biomechanics Of Femoral Neck Locking Platesmentioning
confidence: 99%